Correlation between visual acuity, external limiting membrane and photoreceptor status in patients with neovascular age-related macular degeneration treated with bevacizumab - Ristić, Dragana V; Vukosavljević, Miroslav; Kontić, Marko; Ristić, Petar; Bokonjić, Dubravko; Janićijević-Petrović, Mirjana; Adžić Zečević, Antoaneta; Janićijević, Katarina (Vojnosanitetski pregled, 2017)
Background/Aim. The integrity of outer retinal structures, primarily the photoreceptor layer, is important because of its direct correlation with visual acuity. The aim of this study was to investigate the correlation between best-corrected visual acuity (BCVA), the foveal photoreceptor-inner segment/outer segment (IS/OS) junction and external limiting membrane (ELM) in patients with neovascular age-related macular degeneration (NVAMD) after the treatment with bevacizumab, as well as the correlation between the above-mentioned parameters and different types of neovascular membrane, classified by fluorescein angiography (FA). Methods. The study included 82 patients with NVAMD, treated with intravitreal bevacizumab. All patients underwent a basic ophthalmological examination, FA and optical coherence tomography (OCT). Based on the results of FA, all the patients were divided into two main groups – type I (the occult and minimally classic) and type II (classic and predominantly classic) of the choroidal neovascular membrane (CNV). The OCT images revealed either the presence or the absence of IS/OS and ELM. Results. After the treatment, the mean best corrected visual acuity improved significantly in both groups (p < 0.01). Preserved IS/OS and ELM were registered in a smaller number of patients as compared to the condition before the treatment (p < 0.01). After the treatment, the mean BCVA was significantly better in patients with preserved IS/OS and ELM (p < 0.01). In addition, we registered a higher number of patients with preserved ELM in the first group than in the second group (p < 0.01), whereas there was no significant difference in the integrity of IS/OS between the groups (p > 0.05). Conclusion. The patients with preserved IS/OS and ELM achieved better final visual acuity as compared to the patients without preserved IS/OS and ELM. In our patients, the absence of IS/OS and ELM were more frequent in type II (classic and predominantly classic) CNV than in type I (the occult and minimally classic) CNV.